2008
DOI: 10.4103/0019-509x.44063
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in oral cancer

Abstract: were retrieved from the records. The cases in patients below 40 years of age formed a separate study group. The data obtained was tabulated and comparisons drawn on the observed variables between the two groups. RESULTS: Results showed a high incidence of OSCC among young adults. The demographic and anatomic location of these cases showed signifi cant variations from cases of oral cancer in older patients. In addition, a signifi cant number of these cases failed to show any relation with the commonly implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 0 publications
9
44
1
Order By: Relevance
“…Our present study showed a male preponderance (66.0% vs 34.0%) in OSCC which is in agreement with some earlier studies (Manuel et al, 2003;Sherin et al, 2008;Chang et al, 2013). While increasing number of studies suggest that the proportion of oral cavity cancer cases in women increased worldwide especially among young white individuals in western countries (Patel et al, 2011;Durr et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our present study showed a male preponderance (66.0% vs 34.0%) in OSCC which is in agreement with some earlier studies (Manuel et al, 2003;Sherin et al, 2008;Chang et al, 2013). While increasing number of studies suggest that the proportion of oral cavity cancer cases in women increased worldwide especially among young white individuals in western countries (Patel et al, 2011;Durr et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in agreement with the previous literature on the subject (Sherin et al, 2008;Koo et al, 2013). Conversely, studies in some other Asian countries such as Taiwan, India and Thailand have found that buccal mucosa was a common location which has strongly associated with betel quid chewing habit regionally (Iamaroon et al, 2004;Khovidhunkit et al, 2008;Kaminagakura et al, 2012;Chang et al, 2013;Krishna et al, 2014) Historically, young patients with oral cancers were believed to be particularly aggressive and carry a poor prognosis (Dahlstrom et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…However, (Gangane et al, 2007) reported prevalence of oral malignancies mostly in the 50 to 59 years age group. About 17% of the younger patients are below 40 years of age (Halboub et al, 2011) or at least in the fourth decade of their life (Sherin et al, 2008). A study about Israeli Arab citizens (Avraham et al, 2012) reported, most of the diagnosed oral cancer cases were above 54 years of age (53.7%).…”
Section: Discussionmentioning
confidence: 99%
“…This has generally been attributed to indiscriminate substance abuse, particularly tobacco and related products (smoked and smokeless),, over a considerable period of time (Sherin et al, 2008).…”
Section: Age Distributionmentioning
confidence: 99%
“…Immune competence and the immune cell surveillance diminishes with age which further contributes to the direct relation between age and the malignancy (Derhovanessian et al, 2008). In high incidence countries of the world like India, many cases are diagnosed under the age of 40 years which is attributed to high tobacco consumption starting at relatively young age (Sherin et al, 2008;). …”
Section: Age Distributionmentioning
confidence: 99%